Skønhed i coronapandemiens skygge - Prinds, Christina; Viftrup, Dorte Toudal; Falkø, Erik; Thomsen, Karsten Flemming; Moestrup, Lene; Nissen, Ricko Damberg; Stripp, Tobias Kvist; Søndergaard, Jens; Hvidt, Niels Christian (Tidsskrift for Forskning i Sygdom og Samfund, 2020)
Essay